2021
DOI: 10.3390/children8100888
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome Children, Malocclusion Characteristics and the Need for Orthodontic Treatment Needs (IOTN): A Cross-Sectional Study

Abstract: The purpose of the present study was to assess the characteristics of malocclusion and determine the orthodontic treatment needs of a group of children with Down syndrome. The study group comprised 23 children aged 10–14 years with Down syndrome who were attending special schools. A clinical examination was performed to measure several parameters that assessed malocclusion as well as classifications based on the Index of Orthodontic Treatment Need (IOTN-DC). When the dental health component (DHC) of the IOTN-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Thirty-five studies were cross-sectional [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 50 , 51 ], one was a longitudinal study [ 45 ], and two were retrospective studies [ 28 , 49 ]. Twenty-two studies were conducted in or near Riyadh [ 10 , 11 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 38 ...…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Síndrome de Down é definida com uma alteração de origem genética, onde o paciente apresenta um trio de cromossomos 21, o que permite nomear a variação simultaneamente como trissomia do 21 (DORIGUETTO et al, 2019). Análises genéticas evidenciam que a Síndrome de Down possui etiologia relacionada ao binômio óvuloespermatozoides, que formam os gametas, ou o processo de meiose e mitose cromossômica, que ocorre após a fecundação (ALKAWARI, 2021). O desenvolvimento da síndrome, em uma análise genética, dá-se por três fatores definidos como: trissomia livre do cromossomo 21, translocação entre o cromossomo 21-14, ou 21-22 e em decorrência do desenvolvimento de um mosaico cromossômico (AGHIMIEN; AJAYI; IZE-IYAMU, 2021).…”
Section: Introductionunclassified
“…O autor ressalta que a pseudomacroglossia somado a hipotonia lingual gera o deslocamento dos dentes e da mandíbula. Para Pacurar et al (2018) o agravamento das más oclusões relaciona-se com as combinações entre o retardo do crescimento craniofacial, a disfunção motora e oral, além da hipotonicidade muscular oral generalizada, que levam ao agravamento da condição, porém para Alkawari (2021) pode haver o pseudo classe III entre esses pacientes que apresentam alterações posturais na língua.Aghimien; Ajayi , Ize-iyamu (2021);Sandeepa et al(2021) eAlkawari (2021) entram em concordância quanto ao método de intervenção precoce. Para os autores é possível utilizar a técnica de Expansão Rápida da Maxila (ERM), realizada através de disjuntores fixos, que tende a promover o aumento do espaço interno da cavidade bucal, tendo em vista a capacidade de regularizar atresias maxilares, além de mordidas cruzadas posteriores.…”
unclassified